Wood blocks as a carrier for Saccharomyces cerevisiae cells used in the production of fructose and ethanol. - Guénette, Maryse. (University of Ottawa (Canada), 1993)
Saccharmoyces cerevisiae ATCC 39859 was immobilized onto small cubes of wood in order to produce very enriched fructose syrup from synthetic glucose/fructose mixtures, through the selective fermentation of glucose. The kinetics of growth and ethanol production rates were measured. Several tests to assess the influence of substrate and product concentration on the production rates were carried out and appropriate rate equations were proposed as a design basis for continuous immobilized reactors. The growth and ethanol production rates were found to be inhibited linearly by both substrate and product concentrations. A maximum ethanol productivity of 21.9 g/Lh was attained from a feed containing 10% (w/v) glucose and 10% (w/v) fructose. The ethanol concentration was 29.6 g/L, the glucose conversion was 78% and a fructose yield of 99% was obtained. This resulted in a fructose/glucose ratio of 2.7. At lower ethanol productivity levels the fructose/glucose ratio increases, as does the ethanol concentration in the effluent. The addition of oleic acid, which is known as an anaerobic growth factor, increased the productivity by 13%. The effect of reactor temperature on production rate was studied. Ethanol productivity peaked at 32.6$\sp\circ$C and approached zero near 44$\sp\circ$C. Batch fermentations were carried out using the reactor effluent in an attempt to enhance the ethanol concentration in the effluent from the reactor. The productivity of these processes was not very high due to the low biomass concentration leaving the reactor. The addition of yeast extract or active biomass increased the productivity substantially. The immobilized cell bioreactor was also used to produce sorbitol continuously from fructose. Sorbitol is a polyol which is used as a sweetening agent for diabetics. It is also used in pharmaceutical, foods and chemical industry. A maximum productivity of 3.25 g/Lh was attained from a 133.8 g/L fructose feed, with a fructose conversion of 44%. (Abstract shortened by UMI.)
Keywords: Engineering, Chemical.